Balancing Traditions and Tourism: The Dynamic Roles of Balinese Women - Adnyani, Ni Wayan Giri (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2023)
Tourism significantly influences global economic, social, and environmental landscapes, with women playing a crucial role in its dynamics. Despite their substantial presence in the tourism workforce, women, particularly in Bali, often face disparities in benefiting from their roles. This article employs a phenomenological approach to examine the experiences of Balinese women in the tourism industry, focusing on how they navigate their roles amidst the cultural values inherent to them. The study delves into the dual aspects of their lives, exploring their perceptions and roles in both public and domestic spheres. It aims to uncover the challenges these women face and the potential support mechanisms that could bolster their active participation in the tourism sector. By providing an in-depth analysis of the unique challenges and opportunities encountered by Balinese women, this research offers a comprehensive understanding of their indispensable role within the tourism landscape, set against the backdrop of Bali’s unique cultural and social context. The results showed that there is gradual acceptance and encouragement of women in tourism, providing women with opportunities, and a discernible shift towards a more favorable societal view of women in significant positions. This study emphasizes the need for strategies to address the disparities they face regarding skill development and education, workplace flexibility, and community engagement and support, which are critical areas for policy intervention. It is a call for action, a script for empowerment, and a blueprint for greater involvement in an industry where their presence is not just important but indispensable.